Master track in 10-min resolution and report of the Mustafa Reis Finike cruise as part of the KARST project in the Bay of Antalya (Türkiye), 7.3.2023 - 18.3.2023 - Jasper Hoffmann; Ercan Erkul; Simon Fischer; Jens Schneider von Deimling; Serif Baris; Irfan Yolcubal (PANGAEA, 2024)
Positioning data was acquired using a real-time kinematics (RTK) Global Navigation Satellite System (GNSS) receiver together with an Applanix Wavemaster inertial navigation unit onboard Mustafa Reis Finike during the KARST project. The data were used to receive a validated master track which can be used as a reference for further expedition data. A report with data acquired during the Field Trip in Antalya is also provided.